2014
DOI: 10.1016/j.rmed.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A possible link between increased metabolic activity of fat tissue and aortic wall inflammation in subjects with COPD. A retrospective 18F-FDG-PET/CT pilot study

Abstract: Metabolic activity of the abdominal aorta and visceral fat is increased in COPD patients compared to peers. The degree of visceral fat metabolic activity is associated with aortic inflammation. More prospective research is warranted concerning the role of visceral fat in the development of vascular comorbidity in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Hepatic steatosis develops in the context of increased triglyceride flux into the liver from visceral adipose tissue [41]. Furthermore, fat inflammation, which has been demonstrated in COPD [42], drives the development of NAFLD. Excessive and inflamed visceral fat is associated with circulating cytokines including leptin and TNF-α [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis develops in the context of increased triglyceride flux into the liver from visceral adipose tissue [41]. Furthermore, fat inflammation, which has been demonstrated in COPD [42], drives the development of NAFLD. Excessive and inflamed visceral fat is associated with circulating cytokines including leptin and TNF-α [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…We calculated that 12 patients and 24 controls would provide a power of at least 80% to detect a 20% clinically relevant difference in TBR between groups, assuming a ratio of 2, an SD of 20% and expected mean TBR values of 1 at a two‐sided α level of 0·05 …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Vanfleteren et al reported in a retrospective study that patients with COPD had significantly increased levels of FDG uptake in abdominal VAT based on PET/CT compared to non-COPD controls, whereas abdominal SAT did not significantly differ in the level of FDG uptake. In addition, FDG uptake in abdominal VAT was significantly correlated with FDG uptake in the abdominal aorta, independent of patient age and BMI [26]. However, Christen et al reported in a retrospective study that VAT exhibited higher FDG uptake compared to SAT independent of age, sex, BMI, comorbidities, smoking history, and medications [27].…”
Section: Discussionmentioning
confidence: 99%